Effects of Violent Video Game Exposure on Bullying Perpetration among Young Adults - Dr. Anila Sadaf Mubashir; Rida Kainaat; Mehwish Faryad; Saleha Ahmed (Indus Journal of Social Sciences, 2025)
This study investigated the effects of violent video games exposure on bullying perpetration among young adults, using a sample of 220 participants aged 17-32 year. Cross sectional research design was used. Data were collected through self-reported measures, utilizing the Joren Lemmens Game Addiction Scale (GAS) 2009 and the Cyberbullying Perpetration Scale (CBP) 2015 developed by Jung up Lee. Statistical analyses, including correlation and regression, were conducted to investigate the relationship between violent video games play and bullying behaviors. The results indicate several significant relationships. The GAS is positively correlated with CBP (r = .38, p < .01), suggesting that higher levels of gaming addiction are associated with increased cyber bullying perpetration. GAS also shows a significant positive correlation with Verbal (r = .28, p < .01), Visual (r = .28, p < .05), and Social CBP (r = .48, p < .01). Regression analysis further revealed that violent video game exposure is a significant predictor of bullying perpetration. The regression model accounts for 14% of the variance in cyber bullying perpetration (R = .14, Adj R² = .14). These findings highlight the potential role of violent video games in influencing bullying behaviors among young adults and underscore the importance of monitoring and managing video game content to mitigate its negative impacts on social interactions.